2D SiP nanoflakes as new high-performance lubricant additive for steel/steel sliding contact. (May 2022) - Yu, Tongtong; Xu, Shusheng; Wu, Zishuai; Wang, Daoai
Abstract: Two-dimensional (2D) materials have been studied as lubricant materials for their unique structural characteristics. Here, a 2D SiP single crystal has been grown and its lubricant properties as hexadecane-based additive have been systematically researched. 2D SiP nanoflakes were obtained by using the liquid-phase exfoliation method. The tribological results show that the COF and the wear volume of hexadecane can be remarkably decreased by 30% and 73% under 90 N by adding the 25 mg/L of SiP nanoflakes, respectively. The hexadecane with SiP nanoflakes has larger extreme pressure (3265 MPa) than MoS2 nanoflakes (2709 MPa). Furthermore, it was determined that the weak interlaminar shear interaction and the formation of tribofilm between the sliding interfaces enhance the anti-friction and anti-wear properties.